Justice Denied: Why Was There No Public Inquiry into the Lac-Mégantic Disaster? - Winfield, Mark (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2018)
This paper examines the reasons why, despite the magnitude and significance of the Lac-Mégantic disaster, no formal public inquiry was called into the tragedy. In doing so it explores the substantive and political rationales for establishing public inquiries in circumstances like Lac-Mégantic, and the reasons why the various investigations that have been undertaken by the Transportation Safety Board and others into the disaster do not constitute an adequate substitute for a formal inquiry. The paper then employs a modified institutional-ideological analytical framework to examine the landscape, ideational, societal, and institutional factors that have worked against the calling of an inquiry. The paper concludes that the concept of a formal inquiry likely faced major opposition at the political and official levels within the Government of Canada, as well as major non-governmental actors in the transportation and fossil fuel sectors. Finally, the paper discusses the implications of the decision not to call an inquiry in the Lac-Mégantic case for the role of inquiries in similar circumstances in the future.